EFEKTIVITAS PENYULUHAN DENGAN CERAMAH DAN KONSELING TERHADAP PENGETAHUAN DAN KETERAMPILAN MENYIKAT GIGI PADA SISWA/I SD ISLAM TERPADU AL-FARABI TANJUNG SELAMAT SUNGGAL DELI SERDANG - Yetti Lusiani; Aminah; Sukarsih (Poltekkes Kemenkes Medan, 2022)
Dental hygiene and oral health is important for general health of the body. If someone have dental problems then it will affect to the ability of someone for consuming foods and drinks. If someone have interfere of consuming food and drink it will affect the health of the body. Indonesian citizens still have big problem on dental hygiene and oral health. Data reported that oral health problem keeps increasing in Indonesia. One of oral health problems caused by lack of knowledge regarding oral hygiene and the ability of toothbrushing properly. Knowledge and tooth brushing skill can be obtained by giving dental health education. This study was a quasi experimental using pretest-posttest with control group design. The population in this study were 76 students of SD Islam Terpadu Al-Farabi Tanjung Selamat Sunggal Deli. The purpose of this study was to determine the effect of dental health education by lecturing and counseling towards of knowledge and toothbrushing skill on students of SD Islam Terpadu Al-Farabi tanjong Selamat Sunggal Deli Serdang. Univariate analysis was used to look at frequency distribution each variable and bivariate analysis to analyze knowledge and student skills before and after getting intervention, then Paired t test was used to look at the difference of knowledge and students skill after given dental health education by lecturing and counseling t test independent was used. Based on the results of this study conducted that dental health education by lecturing and counseling is effective to improve the knowledge and students’ toothbrushing skill and reducing student’s OHIS.